STUDY OF THE INFLUENCE OF ELECTROHYDRAULIC DRILLING PARAMETERS ON THE EFFICIENCY OF HARD SOILS DESTRUCTION - Shaimerdenova, K.M.; Nussupbekov, B.R.; Schrager, E.R.; Akhmadiyev, B.A.; Nakipova, S.Zh.; Rakhmankyzy, A. (Eurasian Physical Technical Journal, 2026)
This article examines several aspects of the electrohydraulic drilling method. It presents the results of an experimental study examining the influence of electrohydraulic drilling modes on the efficiency of breaking stone. A brief description and diagram of the experimental setup are provided. Quantitative relationships between the electrical parameters of the optimal mode of electrohydraulic drilling technology for breaking hard soils samples of varying thicknesses are determined. The experimental data confirm the feasibility of achieving significantly higher drilling speeds for vertical wells in hard soil compared to traditional methods.